Watershed Morphometry and Land Characteristics for Watershed Hydrological Response Analysis: A Remote Sensing and GIS-based Approach - Dutta, Dibyendu; Das, S N; Sharma, J R; Radhakrishnan, K (Annals of Arid Zone, 2016)
Remote sensing techniques, tailored with Geographic Information System, were used to study the major hydro-geomorphic variables of seven sub-watersheds (area 53 to 170 km2 each), belonging to the sub-catchment of lower and middle Parbati and Kuho rivers, and to analyze potential soil erodibility and effect of surface condition on erosion. Some of the hydro-geomorphic variables were found to be significantly correlated with each other. Based upon the hydro-morphic and morphometric characteristics and their influence on sediment generation and transport potential, the sub-watersheds were classified into 5 categories (very high to low priority category), and the nature of flood discharge pattern in them was compared. Two sub-watersheds (2D IB3B and 2D IC6C) could be rated as belonging to high priority category. Only 2DIB3B was in medium priority ca~egory, but due to its circular shape,. a sharp run-off peak for short duration could give rise to flash flood. All other sub-watersheds were of oblong to elongated shape and, hence expected to have low and extended flood flow that are easier to control, and belonged to low priority category. Efficient flood control measures are feasible in 2DIC6A and 2DIC6C, but the strategy is expected to be more complex for 2DIB3B.